Scot & soda - McPherson, Catriona, 1965- (McPherson, Catriona, 1965- Last Ditch mystery., 2019)
Now settled in her little houseboat, moored in the slough at the back of the Last Ditch Motel, Lexy Campbell wants nothing more than to build her counseling business, avoid her mother's phone calls and<U+2015>who knows?<U+2015>meet a nice guy. But when she throws a Halloween party for her motley crew of motel pals, the only single man is too old for her, too wrapped up in the case of beer chilling in the slough, and<U+2015>oh, yes<U+2015>too dead. The sensible choice is to leave it up to the cops to identify the body and catch the killer. So faster than you can say "Tam O'Shanter," Lexy and her friends jump into the case themselves, delving deep into their town's past for the roots of a mystifying crime.